Detecção da vespa-da-madeira em pinus taeda no estado de são paulo, Brasil - Wilcken, Carlos Frederico [UNESP]; De Souza, Amanda Rodrigues [UNESP]; Puretz, Barbara De Oliveira [UNESP]; De Camargo, Gabriella Ferreira [UNESP] (FapUNIFESP (SciELO), 2018)
The woodwasp Sirex noctilio (Fabricius) (Hymenoptera: Siricidae) is one of the main pests of Pinus plantations in South America. The aim of this study is to report the occurrence of S. noctilio in Pinus taeda in Botucatu, São Paulo, Brazil. The surveys were carried out in the arboretum of Faculdade de Ciências Agronômicas (FCA) da Universidade Estadual Paulista “Júlio de Mesquita Filho” (UNESP), campus Botucatu, SP where six species of Pinus are distributed in blocks of 100 trees. Resin beads were observed on the trunks and stems of Pinus species. In post-flight evaluation it was reported that 8.77% of P. taeda trees showed symptoms of oviposition by S. noctilio. A female S. noctilio was found performing oviposition. Sirex noctilio is present in Botucatu, increasing the geographical distribution of the pest in São Paulo State.
Detection of pine woodwasp in pinus taeda in são paulo state, Brazil
Keywords: Exotic pest; Forest pest; Occurrence; Pine; Sirex noctilio